Soybean protein isolate/chitosan composite microcarriers for expansion and osteogenic differentiation of stem cells. (1st February 2022) - Ma, Mengjiao; He, Wei; Liu, Xiaotong; Zheng, Yudong; Peng, Jiang; Xie, Yajie; Meng, Haoye; Wang, Yansen
Abstract: Bone tissue has limited ability of self-repair and regeneration. To repair complexly shaped bone tissue defects, chitosan microcarriers (CS microcarriers, being used as cell carriers) impregnated with soybean protein isolate were prepared for expansion and osteogenic differentiation of stem cells. Highly soluble 7S and 11S powders were obtained through purification and separation of soy protein by adopting Nagano. Pure CS microcarriers were prepared by using an anti-phase suspension combined with thermally induced phase separation technique. Thereafter, CS microcarriers was impregnated into 11S, 7S and SPI solution, forming 11S/CS, 7S/CS and SPI/CS composite microcarriers. The morphology, pore size, porosity and surface potential of the composite microcarriers were investigated. The microcarriers are all three-dimensional porous structures. Compared with CS and SPI/CS microcarriers, 11S/CS and 7S/CS composite microcarriers showed porous structures and high porosity with large pores. Thereafter, rat adipose-derived mesenchymal stem cells (rADSCs) were cultured on composite microcarriers for 14 days to evaluate the effect of composite microcarriers on stem cells proliferation and osteogenic differentiation ability. The outcomes show that composite microcarriers better-supported cell adhesion and proliferation than CS microcarriers. In addition, there were more cells inside 11S/CS and 7S/CS composite microcarriers than those of CS, SPI/CS microcarriers. Alkaline phosphatase (ALP), collagen type I (COLI) and Alizarin Red S staining showed that the addition of soybean protein isolate components could promote osteogenic differentiation of rADSCs.